Las intervenciones socioemocionales para desarrollar la resiliencia en niños y niñas de 3 a 5 años - Aviles Taris, Laura (2025)
The article considers the importance of socio-emotional intervention programs in children from 3 to 5 years old, where the central problem is the need to improve capacities and resilience skills in them, as this population is critical of adverse changes in the family, educational, and community context that are affected by factors: poverty, chronic malnutrition, parental abandonment, child abuse and violence. The purpose is to analyze how socio-emotional interventions improve resilience, socio-affective skills, mental health and comprehensive well-being in children. The methodology used is descriptive, bibliographic review, based on the PRISMA 2020 protocol, 7 databases were identified (Web of Science, Scopus, Springer Nature, PubMed, Redalyc, Scielo and Latindex), with 89 articles reviewed after meeting the inclusion and exclusion criteria that allowed us to discern the relevant and implemented studies to develop resilience and socio-emotional skills. Among the results, the effectiveness of the PATHS, Incredible Years programs and practices based on play, yoga and storytelling, where they achieved significant improvements in self- control, empathy and problem solving, as well as "forest bathing", for social cohesion and psycho- emotional well-being. In conclusion, socioemotional interventions make it possible to mitigate the impact of adverse factors and develop a resilient personality in childhood. However, limitations in longitudinal studies and a deficit of specific research in the Latin American context are identified, which highlights the need for inclusive approaches adapted to local realities to guarantee a sustainable impact.